(untitled) (Journal of Medicine, 2017)
Strongyloidiasis is a helminthic disease which is common in the tropics, subtropics and especially prevalent in far east. It is rarely reported in Bangladesh probably due to the low index of suspicion in common practice. We are reporting a case of strongyloidiasis that was found in a middle-aged patient presenting with diarrhoea, weight loss and generalized itching. He was treated in different hospitals and undergone extensive investigation. We diagnosed him as a case of strongyloidiasis on the basis of stool microscopy examination and treated with Ivermectin. J MEDICINE Jan 2018; 19 (1) : 54-57